2021
DOI: 10.47191/ijsshr/v4-i5-11
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Green Supply Chain (GSC) Adoption Model, MENA Developing countries Empirical Study

Abstract: Green supply chain management is attracting attention as a way to decrease the adverse environmental effects of industries worldwide. GSCM practices are considered as environmentally friendly practices, which include water efficiency, energy efficiency, waste management, environment conservation, recycling and reuse, toxic substance management and hazardous and optimization of transportation. However, considering the context of an emerging economy, green supply chain management is still in its inception and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The adoption of a green supply chain is a complex process that requires consideration of many aspects (Hsu & Hu, 2008). The technological factor of the TOE framework demands that organizations to adopt innovations and technologies related to better performance and higher economic gains (Hanna et al, 2021), i.e. how much these technologies are consistent with the present structure and requirements (Rogers, 2010).…”
Section: Technological Factors and Sustainable Green Practicesmentioning
confidence: 99%
“…The adoption of a green supply chain is a complex process that requires consideration of many aspects (Hsu & Hu, 2008). The technological factor of the TOE framework demands that organizations to adopt innovations and technologies related to better performance and higher economic gains (Hanna et al, 2021), i.e. how much these technologies are consistent with the present structure and requirements (Rogers, 2010).…”
Section: Technological Factors and Sustainable Green Practicesmentioning
confidence: 99%
“…Adopting GH and GTI strengthens an organization's capacity to drive GSCM (Pham et al, 2019a). GSCM, on the other hand, cannot be implemented without adequate organizational support (Hanna et al, 2021) and these two practices are viewed as the primary drivers of GSCM (Jabbour and de Sousa Jabbour, 2016).…”
Section: Role Of Ghrmps Andmentioning
confidence: 99%
“…However, research by (Shee et al, 2021) has shown that the use of information and communication technologies and the capacity of information technology have a positive effect on smart logistics. In addition, (Dadhich & Hiran, 2022) also reported that economic, social, technological, and organizational factors were positively related to organizational performance via the environmental sustainability of firms (Chege & Wang, 2020;Alraja et al, 2022;Aboelmaged, 2018;Hanna et al, 2021;Shee et al, 2021;Yavuz et al, 2023;Karmaker et al, 2022;Contini et al, 2023). (Al-Ashmori et al, 2022) show that there are different models that explain the acceptance and implementation of innovative applications, such as the Technology Readiness Index, the Planned Behavior Theory, the Task Fit Technology Model, the Unified Technology Acceptance and Use Theory, the Technology Acceptance Model.…”
Section: Literature Reviewmentioning
confidence: 99%